Hidden Global Causes of the Global Financial Crisis - Brusov, Peter; Filatova, Tatiana; Eskindarov, Mukhadin; Orekhova, Natali (Journal of Reviews on Global Economics, 2012)
Abstract: Hopes of ending the financial crisis did not materialize. Recent events (the problems of the euro zone, the threat of default in the U.S., the collapse of the financial market after a reduction of the credit rating of the U.S., debt problems in the world (Europe, U.S.), U.S. fiscal cliff, etc.) show that the crisis deepened, affecting new areas and taking on a systemic character. It becomes clear that we need in-depth analysis of its general, systemic causes. This article examines recent results in this field, obtained by scientists of Finance University under the Russian Federation Government.